НІМЕЦЬКА КУЛЬТУРНА ТРАДИЦІЯ ЧЕРЕЗ СПРИЙНЯТТЯ МОВИ (Zaporizhzhia Historical Review, 2021)
The article deals with the German language picture of the world, which is the reflection of the German people culture, their mentality and history of development. All these factors influence all language layers: semantics, syntax, morphology, lexicology. The German language with its variability and grammar closedness reflects the cultural tradition of Germany.